Texas standoff eaudiobook - Kelton, Elmer (Elmer Kelton's Texas Rangers, 2011)
In Elmer Kelton's Texas Standoff, Ranger Andy Pickard and his partner, Logan Daggett, are sent to central Texas to investigate a series of killings and cattle thefts. The two biggest cattlemen in the area blame each other for the violence, but it seems to Andy that neither man may be guilty. The case is complicated by the rise of a gang of "regulators"—masked vigilantes—and the arrival of a notorious hired gunman whose employer is unknown. The murder of a captured regulator and a standoff in the county jail wind up bringing to justice the men responsible for the killings and thievery. Among the culprits is a man whose guilt no one would have guessed, and among the ironies of the case is a telegram to the Rangers from the State of Texas notifying them that their services are no long required.